Manajemen Mutu di Sekolah Unggul Di SMAN 1 Banjarmasin dan SMAN 7 Banjarmasin - Ayu Mutia Sari; Ahmad Suriansyah; Sulaiman Sulaiman (Journal Of Administration and Educational Management (ALIGNMENT), 2024)
This research aims to analyze the implementation of quality management and the obstacles faced in its implementation, as well as the efforts to follow up on the challenges faced in two superior public high schools in Banjarmasin. This qualitative research uses descriptive methods like interviews, observation, and documentation. Apart from that, the subjects of this research were the leadership, the quality assurance department, the deputy head, and several teachers. The research results show that the implementation of quality management at SMAN 1 Banjarmasin and SMAN 7 Banjarmasin has been carried out based on the five pillars of quality schools: customer focus, total participation, measurements, commitment, and continuous improvement. Furthermore, the obstacles faced in implementing superior school quality management by SMAN 1 Banjarmasin are related to student input and limited funds to carry out student activities. Meanwhile, the obstacles faced by SMAN 7 Banjarmasin are related to limited funds, lack of student participation in class, and the need to increase teacher motivation in developing competence. Furthermore, efforts were made to follow up on the obstacles faced in implementing school quality management, especially in increasing teacher competency, and encourage teachers to participate in training activities to improve their competency. In conclusion, quality management at SMAN 1 Banjarmasin and SMAN 7 Banjarmasin has been implemented based on five pillars of quality schools: customer focus, total participation, measurements, commitment, and continuous improvement. Keywords: Customer Focus, Commitment, Continuous Improvement, Excellent Schools Quality Management, Measurements, Total Participation